The exploration of migration flows in Greece, Spain, Portugal and Italy during the economic crisis - Καλογεράκη, Στεφανία (The Greek Review of Social Research, 2017)
The recent global financial and economic crisis has multiple impacts which, between others, include changes in international migration flows. The present study using secondary data analysis explores migration inflows and outflows across EU member-states most severely affected, including Greece, Spain, Portugal and Italy. The findings verify the experience of previous recessions indicating similar trends. However, important differences are detected indicating that international flows are formed from additional factors which are not associated with the economic crisis per se but reflect the peculiarities and migration characteristics of each country as well as broader events that operate independently of the economic conditions